2004
DOI: 10.2202/1538-0653.1136
|View full text |Cite
|
Sign up to set email alerts
|

Do Unbundling Policies Discourage CLEC Facilities-Based Investment

Abstract: An expanding economics literature has examined the theoretical linkages between mandatory unbundling in the telecommunications sector and the incentives to invest in facilities by both incumbent local carriers and competitive carriers. Recent empirical evidence that substantiates the theory has emerged. That literature documents CLECs’ reluctance to make facilities-based investments instead of availing themselves of incumbents’ UNEs at low regulated prices that are based on total element long-run incremental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 2 publications
0
33
0
Order By: Relevance
“…They find that the number of unbundled DSL connections per capita is negatively correlated with the number of fibre connections. Similarly, Briglauer et al (2011) 20 16 See for example Crandall et al (2004) or Hausman, J. and G. Sidak (2005): "Did mandatory unbundling achieve its purpose? Empirical evidence from five countries" Journal of Competition Law and Economics, 1(1), 173-245.…”
Section: The Empirical Evidence Of the Loi Theorymentioning
confidence: 99%
“…They find that the number of unbundled DSL connections per capita is negatively correlated with the number of fibre connections. Similarly, Briglauer et al (2011) 20 16 See for example Crandall et al (2004) or Hausman, J. and G. Sidak (2005): "Did mandatory unbundling achieve its purpose? Empirical evidence from five countries" Journal of Competition Law and Economics, 1(1), 173-245.…”
Section: The Empirical Evidence Of the Loi Theorymentioning
confidence: 99%
“…6 station mt is the number of the stations which NTT adopted the …ber-optic lines. We use this variable as the measurement of quantity of NTT's line.…”
Section: Linear Regression Modelsmentioning
confidence: 99%
“…When …rms with no 6 We divided by number of households, because oftenly when number of households increase, number of user …rms increase. However, there are possibility the divsion of family caused the negative e¤etct, because the number of user …rms increase concavely.…”
Section: Linear Regression Modelsmentioning
confidence: 99%
“…Regulation that increased incentives for entry over existing networks could undermine incentives for new, facilities-based entry. For example, a study by Crandall et al (2004) showed that lower rates for unbundled network elements led to less facilities-based entry by competitive telephone companies. Also, if vertical foreclosure is in fact profit maximizing, then unbundling and open access could distort the investment incentives of the incumbent conduit.…”
Section: Arguments For and Against Unbundling And Open Accessmentioning
confidence: 99%